2004
DOI: 10.1142/s1363246904001651
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

DAVID M. BOORE

Abstract: Large modifications of seismic waves are produced by variations of material properties near the Earth's surface and by both surface and buried topography. These modifications, usually referred to as "site response", in general lead to larger motions on soil sites than on rock-like sites. Because the soil amplifications can be as large as a factor of ten, they are important in engineering applications that require the quantitative specification of ground motions. This has been recognised for years by both seism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Consider, for example, a model that predicts ground accelerations as a function of earthquake size (magnitude) and the distance of the recording site from the source of the earthquake. The residuals of the recorded accelerations relative to the predictions define the aleatory variability in the predictions, but this variability will be appreciably reduced if the nature of the surface geology at the recording sites is taken into account, even if this is just a simple distinction between rock and soil sites (Boore 2004). In effect, such a modification to the model isolates an epistemic uncertainty-the nature of the recording site and its influence on the ground acceleration-and thus removes it from the apparent randomness; this, in turn, creates the necessity, when applying the model, to obtain additional information, namely the nature of the surface geology at the target site.…”
Section: Randomness and Uncertaintymentioning
confidence: 99%
“…Consider, for example, a model that predicts ground accelerations as a function of earthquake size (magnitude) and the distance of the recording site from the source of the earthquake. The residuals of the recorded accelerations relative to the predictions define the aleatory variability in the predictions, but this variability will be appreciably reduced if the nature of the surface geology at the recording sites is taken into account, even if this is just a simple distinction between rock and soil sites (Boore 2004). In effect, such a modification to the model isolates an epistemic uncertainty-the nature of the recording site and its influence on the ground acceleration-and thus removes it from the apparent randomness; this, in turn, creates the necessity, when applying the model, to obtain additional information, namely the nature of the surface geology at the target site.…”
Section: Randomness and Uncertaintymentioning
confidence: 99%
“…Concerning aleatory uncertainty, it is difficult to reduce it even for regions with dense seismic arrays and large databases of strongmotion records (Douglas 2003). In recent studies, it is observed that the effect of various parameters such as site classes Vs30, fault type on aleatory uncertainty is very low (e.g., Boore 2004, Bommer et al 2003. The large aleatory variability is accounted for using simple models in GMPEs for defining complex phenomena (Bommer and Abrahamson 2007).…”
Section: Introductionmentioning
confidence: 99%